A K2Fe4O7 superionic conductor for all-solid-state potassium metal batteries. Issue 18 (23rd April 2018) - Yuan, Hongming; Li, He; Zhang, Tingsong; Li, Guanghua; He, Tianmin; Du, Fei; Feng, Shouhua
Abstract : Potassium ferrite exhibits super-high ionic conductivity for all-solid-state potassium metal batteries. Abstract : A new 3D open-framework potassium ferrite, K2 Fe4 O7 (1 ), has been successfully synthesized under hydrothermal conditions. The framework of1 consists of both FeO6 octahedral and FeO4 tetrahedral units with shared vertices and edges where there are 6- and 3-ring channels parallel to the trigonal a - and c -axes, enabling many highly mobile potassium ions to move quickly through the channels. The K + ion conductivity of the polycrystalline sample was 5.0 × 10 −2 S cm −1 at room temperature. Interestingly, conductivities along the a -axis direction in single crystal K2 Fe4 O7 reached 3.5 × 10 2 S cm −1 at 25 °C and 5.0 × 10 2 S cm −1 at 500 °C with an activation energy of 0.08 eV. The conductor possessed a wide voltage stability up to 5 V vs. K/K + . Using the K2 Fe4 O7 electrolyte, we demonstrate an all-solid-state potassium metal battery employing a Prussian blue cathode with a high charge/discharge rate of 250C (charge/discharge in 14 s, 1C = 87 mA h g −1 ).